2022
DOI: 10.18502/ijm.v14i2.9195
|View full text |Cite
|
Sign up to set email alerts
|

Iodine induces toxicity against Candida albicans and Candida glabrata through oxidative stress

Abstract: Background and Objectives: Candida species are antifungal-resistant opportunistic infections that spread through contami- nated medical staff hands and hospital surfaces creating a nosocomial infection risk. Iodine´s antibacterial properties are well established; however, its antifungal properties remain unknown. The objective of this study was to investigate the antifungal effects of lugol on cell viability and oxidative stress on Candida albicans and Candida glabrata strains. Materials and Methods: MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Intrinsic mechanisms include natural properties of a fungal cell, such as decreased permeability, stimulated activity of efflux pumps, repair mechanisms, phenotypic modulation, and inactivation of biocides [30]. Cuellar-Rufino et al [31] reported that C. albicans and C. glabrata lacking catalase gene (cta1) and superoxide dismutase 1 and 2 double mutants (sod1∆, sod2∆) strains, exposed to 10 mM of lugol, showed a significant increase in antioxidant enzymes activity, similar to that induced with the presence of catalase and superoxide dismutase. Additionally, superoxide dismutase 1 and 2 double mutants (sod1∆, sod2∆) of C. glabrata were more susceptible to lugol treatment in relation to the parental strain.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic mechanisms include natural properties of a fungal cell, such as decreased permeability, stimulated activity of efflux pumps, repair mechanisms, phenotypic modulation, and inactivation of biocides [30]. Cuellar-Rufino et al [31] reported that C. albicans and C. glabrata lacking catalase gene (cta1) and superoxide dismutase 1 and 2 double mutants (sod1∆, sod2∆) strains, exposed to 10 mM of lugol, showed a significant increase in antioxidant enzymes activity, similar to that induced with the presence of catalase and superoxide dismutase. Additionally, superoxide dismutase 1 and 2 double mutants (sod1∆, sod2∆) of C. glabrata were more susceptible to lugol treatment in relation to the parental strain.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect contact through contaminated surfaces Povidone-iodine has antifungal properties, effectively killing Candida albicans and preventing its transmission. (20) Herpes simplex virus (HSV) Direct contact through oral lesions or saliva Povidone-iodine decreases the risk of transmission and recurrence by exhibiting virucidal action against HSV. Khalifa et al, 2022 (21) Human papillomavirus (HPV)…”
Section: Candida Albicansmentioning
confidence: 99%